EFFECT OF GIVING INDIGOFERA (Indigofera zollingeriana) LEAF JUICE THROUGH DRINKING WATER ON THE INTERNAL ORGAN OF MALE BALI DUCKS (Anas platyrhynchos) - V. O., Silaban; Puger, A. W.; Warmadewi, D. A. (Jurnal Peternakan Tropika, 2024)
Research aimed to determine the effect of giving indigofera leaf juice through drinking water on the internal organs of male Bali ducks aged 8 weeks has been carried out at Sesetan Farm Street Sesetan, Denpasar, Bali. The design used was a completely randomized design (CRD) consisting of four treatments, namely: P0 (without indigofera leaf juice in drinking water), P1 (giving 2% indigofera leaf juice in drinking water), and P2 (giving 4% indigofera leaf juice). indigofera in drinking water), P3 (Giving 6% of indigofera leaf juice in drinking water). Each treatment consisted of 5 replications and each replication used 6 bali ducks so that there were 120 male bali ducks aged two weeks. The variables observed were weight and percentage of heart, liver, proventriculus, ventriculus, and bile. The results showed that the administration of indigofera leaf juice as much as 2%, 4% and 6% was not significantly different (P>0.05) on all weight and percentage of internal organs. Based on the results of the study, it can be concluded that the administration of indigofera leaf juice to a level of 6% had no effect on the weight and percentage of internal organs (heart, liver, proventriculus, ventriculus, and bile) of male bali ducks aged 8 weeks.